Heat transfer behavior in ultrahigh-speed continuous casting mold - Zhang Luping (De Gruyter, 2021)
The growth rate of the shell thickness in the funnel mold for ultrahigh-speed continuous casting of steel has a significant effect on the shell surface quality. By using the node temperature inheritance algorithm, a three-dimensional transient thermal conductivity model of the liquid steel solidification inside the mold was established, and the effects of casting temperature and speed on the heat transfer behavior of the thin slab were investigated. The results show that with an increase in the casting speed from 4.0 to 6.0 m·min−1, the maximum thickness of the shell at mold exit was reduced from 26 to 12.8 mm, and the maximum temperature of the slab surface at mold exit increased from 1,210 to 1,305°C. However, the increase of casting temperature from 1,550 to 1,560°C had little effect on the surface temperature and thickness of the slab shell.